The role of diaspora network in ethnic entrepreneurial process : Vietnamese entrepreneurs in Finland - Nguyen, Mach (My University, 2019)
Immigration and emigration have been a global sensation for a long time, especially during the last centuries since many worldwide incidents including wars and economic crisis have occurred. In the host country, immigrants face various disadvantages such as language barrier, “non-equivalency” and “non-recognition” in education and experience, which lead to difficulties to be employed. Hence, ethnic entrepreneurship has become one of the most effective methods to create job opportunities as well as facilitate integration for the ethnic communities. Another side product of immigration is the creation of diaspora communities - which consist of members that share the same identity such as ethnic, religion, or origin, the social connection among the members of those groups is called diaspora network. The purpose of this study is to investigate the role of diaspora network throughout the ethnic entrepreneurial process including three phases: idea development and preparation; implementation; operation and growth. The literature review of the research includes theoretical background on the entrepreneurial process and the effects of diaspora network in ethnic entrepreneurship. All the components are then synthesized into one theoretical framework, which is used as a foundation for the empirical study. The qualitative research method was selected for the study to provide an in-depth view on the experiences of the ethnic entrepreneurs. Four semi-structured interviews with Vietnamese ethnic entrepreneurs in Finland were conducted to collect data for further analysis. The findings of the empirical analysis have confirmed that diaspora network has both positive and negative effects on the ethnic entrepreneurship. The most highlighted impact from the analysis is the importance of human resources from the diaspora network. However, the ethnic entrepreneurs do not rely on their co-ethnic group as the main source of information or financial assistance. And because of the small population of the diaspora group, this is not the main market segment for the ethnic entrepreneurs either. The early time of the business is when the ethnic entrepreneurs are more likely to reach out for support from their diaspora community. The study provides some theoretical contribution on the different influences of diaspora network on the ethnic entrepreneurs and also practical implications to policy makers and other organizations to help facilitate the ethnic entrepreneurial process. It also suggests that other features of diaspora should be taken into account to better understand this phenomenon.
Keywords: ethnic entrepreneurship, diaspora network, entrepreneurial process